EDUCATIONAL INSTITUTIONS AND THE QUALIFICATIONS OF BEING A TEACHER IN THE DIGITAL AGE: A CASE STUDY OF THE CENTRAL REGION OF THAILAND - Silichantho, Sengsavanh; Jaroenphuwadon, Manutdon (RMUTT GLOBAL BUSINESS ACCOUNTING AND FINANCE REVIEW, 2021)
This qualitative research is intended to study the purposes of the development of educational institutions and suitable qualifications for teachers in the digital age. Research instrument was a semi-structured questionnaire which was used for depth interviews. The study samples were 20 education administrators from 10 educational institutions under the Ministry of Education in Thailand. The data was collected until it was saturated. The results indicated that the educational institutions want to develop learners to achieve three characteristics as follows: 1) Intelligence, mind, and healthy body;2) Good citizenship, self-sufficiency, and responsibility; and 3) Social and environmental development. In addition, the result also indicated that the characteristics of teachers in the digital age consisted of four points of view as follows: 1) The teachers in the digital age must be a person with knowledge of what to teach and experience; therefore, teachers in the digital age cannot teach according to the textbook only. 2) The teachers must have good internet and computer skills because all knowledge of the current era is about the internet and computer. 3) The teachers must be able to communicate in English. and 4) The teachers must be a person with morality and ethics, being ashamed of sin and act as a good role model for their students and society.